Educational ideas of President Bienvenido M. Gonzalez - Lazaro, Guillermo R. 1924- (1955)
The educational ideas of Bienvenido M. Gonzalez was the subject of this study. Here, his ideas were presented objectively, and to make the presentation comprehensive and vivid, the investigator limited the problem to five major topics namely: his views on the educational philosophy of the Constitution, his views on the various phases of the Philippine educational system, his views on the teacher, his ideas on the University of the Philippines and his views on some educational issues